2022
DOI: 10.7759/cureus.32886
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis on Possible Role of Vitamin C in Sepsis

Abstract: Sepsis is a substantial healthcare burden, and its management continues to be a major challenge. Prior studies demonstrate conflicting evidence regarding the utility of vitamin C in sepsis. This systematic review and meta-analysis aim to collect data among critically ill patients (sepsis/septic shock), comparing the efficacy of parenteral vitamin C with standard care.A literature review was conducted using databases including PubMed, Web of Science, Google Scholar, and the Cochrane Library to identify randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Three of recent systematic reviews showed reduction in overall mortality with vitamin C mono‐ or combination‐therapy, but certainty of evidence was evaluated as very low, 6 low, 2 or moderate 4 . Other studies did not find firm evidence for a difference in mortality 1,3,5 . One weakness of these studies, including the present review, is the large number of outcomes, including mortality, being evaluated at multiple timepoints, which may increase the risk of identifying effects due to chance alone.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Three of recent systematic reviews showed reduction in overall mortality with vitamin C mono‐ or combination‐therapy, but certainty of evidence was evaluated as very low, 6 low, 2 or moderate 4 . Other studies did not find firm evidence for a difference in mortality 1,3,5 . One weakness of these studies, including the present review, is the large number of outcomes, including mortality, being evaluated at multiple timepoints, which may increase the risk of identifying effects due to chance alone.…”
Section: Discussionmentioning
confidence: 76%
“…4 Other studies did not find firm evidence for a difference in mortality. 1,3,5 One weakness of these studies, including the present review, is the large number of outcomes, including mortality, being evaluated at multiple timepoints, which may increase the risk of identifying effects due to chance alone. Use of mortality outcomes at multiple timepoints is one of the major weaknesses in our review but is inherent to the current body of evidence on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the studies are small, several studies are observational and the clinical significance of the findings is often uncertain. Some examples are given below 8 14–28…”
Section: Can Parenteral Vitamins Treat or Prevent Disease?mentioning
confidence: 99%